Pharmacokinetic and pharmaceutic interaction between digoxin and Cremophor RH40 - Tayrouz Haffar, Yorki Antoine; Ding, Reinhard; Burhenne, Jürgen; Riedel, Klaus-Dieter; Weiß, Johanna; Hoppe-Tichy, Torsten; Haefeli, Walter E.; Mikus, Gerd (Clinical pharmacology & therapeutics, 2003)
Background The pharmacokinetics of digoxin is modulated by the efflux pump P-glycoprotein. Cremophor EL (BASF Aktiengesellschaft, Ludwigshafen, Germany) (polyoxyl 35 castor oil), a castor oil derivative used to improve the solubilization of drugs and vitamins, has been shown to inhibit this membrane transporter in vitro and in vivo. So far, no study in humans has evaluated the effect of Cremophor RH40 (BASF Aktiengesellschaft) (polyoxyl 40 hydrogenated castor oil) on P-glycoprotein. Methods A randomized, double-blind, placebo-controlled crossover study in 12 healthy individuals was performed with a single oral dose of 0.5 mg digoxin in a hard gelatin capsule in combination with multiple doses of oral Cremophor RH40 (600 mg 3 times daily) or placebo. A digitized electrocardiogram with 12 standard leads was recorded to assess the pharmacodynamics of digoxin. Results Cremophor RH40 delayed and enhanced the absorption of digoxin in the first 5 hours after dosing. During Cremophor RH40 administration, digoxin lag time was significantly prolonged compared with placebo (0.53 ± 0.25 hour versus 0.36 ± 0.19 hour, P = .04). The peak concentration of digoxin increased by 22%, from 2.21 ± 0.94 ng/mL to 2.69 ± 1.28 ng/mL (P = .06). Similarly, the area under the plasma concentration-time curve from 0 to 5 hours significantly increased by 22% (5.23 ± 1.63 h · ng/mL versus 4.30 ± 1.12 h · ng/mL, P = .03). Digoxin did not cause a clinically significant change in the dynamic parameters during both periods. Conclusion This study demonstrates a pharmacokinetic and pharmaceutic interaction between the emulgent Cremophor RH40 and digoxin, caused by P-glycoprotein inhibition and prolongation of the dissolution time of digoxin tablets by Cremophor RH40, respectively. Our in vivo study in humans supports the validity of in vitro observations on P-glycoprotein. Clinical Pharmacology & Therapeutics (2003) 73, 397-405; doi: 10.1016/S0009-9236(03)00059-6